OP22 Antibody decay, T cell immunity and breakthrough infections following SARS-CoV-2 vaccination in infliximab- and vedolizumab-treated patients. (21st January 2022) - Lin, S; Kennedy, N A; Saifuddin, A; Muñoz Sandoval, D; Reynolds, C J; Seoane, R C; Kottoor, S H; Pieper, F P; Lin, K M; Butler, D K; Chanchlani, N; Nice, R; et al.
Abstract: Background: Antibody responses following SARS-CoV-2 infection or a single-dose of SARS-CoV-2 vaccine are impaired in patients with inflammatory bowel disease treated with anti-TNF compared to those treated with vedolizumab, a gut-selective anti-integrin α4β7 monoclonal antibody. Here we sought to determine if patients treated with infliximab have attenuated serological and T cell responses and an increased risk of breakthrough COVID-19 infection following primary SARS-CoV-2 vaccination. Methods: Anti-spike (S) receptor binding domain (RBD) antibody concentration in 2306 infliximab-treated patients were compared to a cohort of 1045 vedolizumab-treated patients. Our primary outcome was anti-S RBD antibodies 2 to 10 weeks after a second dose of the BNT162b2 or ChAdOx1 nCoV-19 vaccines. Secondary outcomes were anti-spike T cell responses, durability of vaccine responses and risk of breakthrough infections following two doses of vaccine. Results: Anti-S RBD antibody concentrations were lower in patients treated with infliximab than in those treated with vedolizumab, following a second dose of BNT162b2 (567.3 U/mL [6.1] vs 4601.1 U/mL [5.3], p <0.0001) and ChAdOx1 nCoV-19 (183.9 U/mL [5.0] vs 789.4 U/mL [3.5], p <0.0001) vaccines (Fig. 1). Vaccination with the BNT162b2 vaccine compared to the ChAdOx1 nCoV-19 was independently associated with a 3.7-fold [95% CI 3.30 – 4.13] higher anti-S RBD antibody concentration (p < 0.0001) (Fig. 2). There were no significant differences in the magnitude of anti-spike T cell responses observed in infliximab- compared with vedolizumab-treated patients after one or two doses of either vaccine. Antibody half-life was shorter in infliximab- than vedolizumab-treated patients following two-doses of BNT162b2 (4.0 weeks [95% CI 3.8 – 4.1] vs 7.2 weeks [95% CI 6.8 – 7.6]) and ChAdOx1 nCoV-19 (5.3 weeks [95% CI 5.1 – 5.5] vs 9.3 weeks [95% CI 8.5 – 10.2], p value < 0.0001). Breakthrough SARS-CoV-2 infections were more frequent (5.8% (202/3467) vs 3.9% (66/1691), p = 0.0032) and the time to breakthrough shorter in patients treated with infliximab than vedolizumab (p = 0.0023) (Fig. 3). Higher anti-S RBD antibody concentrations following a second dose of SARS-CoV-2 vaccine protected against breakthrough SARS-CoV-2 infection: overall, for every 10-fold rise in anti-S RBD antibody level we observed a 0.8-fold reduction in odds of breakthrough infection ([95% CI 0.70 – 0.99], p = 0.035). Conclusion: Infliximab was associated with attenuated, less durable vaccine induced anti-S RBD antibody responses and a 50% increase in breakthrough SARS-CoV-2 infection. Further follow-up is required to assess whether third primary doses can mitigate the effects of infliximab on anti-S RBD antibody responses.